RESEARCH OF STACKELBERGS GAMETHEORY MODEL PERSPECTIVES INHOLICSTIC MEDICINE - BARYSHYCH, LUKA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents an analysis of the use of the Stackelberg model for modeling and analyzing leadership-evolutionary population systems in medicine. The current trends in the use of game theory in the management of patients during chemotherapy are analyzed. The concept of holistic medicine and the possibilities of further integration and development of the Stackelberg model are outlined.The intersection of game theory and medicine has become a promising avenue for understanding and managing complex systems, particularly in the context of chemotherapy and patient care. This paper  explores the analysis of leadership-evolutionary population systems in medicine using the Stackelberg model. It delves into current trends in the application of game theory within patient management during chemotherapy, shedding light on the potential of holistic medicine and the integration of the Stackelberg model for further advancements in this field.The Stackelberg model, a cornerstone in game theory, has proven valuable in modeling and analyzing leadership dynamics within evolving population systems. In the medical context, its application offers insights into strategic interactions among stakeholders, influencing the trajectory of patient care during chemotherapy. The paper examines the intricacies of the Stackelberg model, emphasizing its role in understanding decision-making processes and optimizing resource allocation in healthcare settings.Further improvement of approaches to the use of game theory models in the analysis, simulation and management of processes in medicine requires the adoption of an arsenal of concepts and tools from the holistic theory of medicine. Current models, including those by Stackelberg, have limited capabilities to assess the evolutionary system's resistance to the actions of an external agent.An in-depth analysis of current trends reveals a growing reliance on game theory for patient management during chemotherapy. Game-theoretic approaches enable healthcare professionals to anticipate and respond to evolving situations, fostering more effective and adaptive strategies. This section explores real-world examples and success stories where game theory has played a pivotal role in optimizing treatment plans and improving patient outcomes.Despite the advancements made through the integration of the Stackelberg model and holistic medicine, challenges persist. This paper addresses limitations in current models, emphasizing the need for a broader conceptual framework to evaluate evolutionary systems' resilience to external influences. It calls for continued research and innovation in incorporating holistic principles into game theory models, envisioning a future where healthcare management is characterized by a more nuanced and adaptive approach.
Keywords: evolutionary game theory; holistic medicine; Stackelberg model